2019
DOI: 10.1016/j.chest.2019.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of Time in Range 70 to 139 mg/dL Is Associated With Reduced Mortality Among Critically Ill Patients Receiving IV Insulin Infusion

Abstract: BACKGROUND: In addition to hyperglycemia, hypoglycemia, and glycemic variability, reduced time in targeted blood glucose range (TIR) is associated with increased risk of death in critically ill patients. This relation between TIR and mortality may be confounded by diabetic status and antecedent glycemic control. METHODS: This study retrospectively analyzed critically ill patients managed with the same IV insulin protocol at multiple centers. The percentage of TIR between 70 and 139 mg/dL was calculated. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 41 publications
5
54
0
1
Order By: Relevance
“…5,6 Hyperglycemia was once considered an adaptive response essential for survival and therefore not routinely controlled, 7 but numerous observational studies have provided evidences which supported a link between hyperglycemia and poor prognosis of critically ill patients. 2,[8][9][10][11][12][13][14][15] Now it is well accepted that glycemic control plays an important role in the management of patients in ICU, 16 but it is still controversial what the optimal blood glucose range is. 17,18 Evidences from several clinical trials which investigated various ranges of blood glucose in various populations of ICU patients supported different target blood glucose, and are sometimes contrary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Hyperglycemia was once considered an adaptive response essential for survival and therefore not routinely controlled, 7 but numerous observational studies have provided evidences which supported a link between hyperglycemia and poor prognosis of critically ill patients. 2,[8][9][10][11][12][13][14][15] Now it is well accepted that glycemic control plays an important role in the management of patients in ICU, 16 but it is still controversial what the optimal blood glucose range is. 17,18 Evidences from several clinical trials which investigated various ranges of blood glucose in various populations of ICU patients supported different target blood glucose, and are sometimes contrary.…”
Section: Introductionmentioning
confidence: 99%
“…include study populations under specific and strict criteria, of which the characteristics may be quite different to the general population, and that the clinical practice and patient characteristics in ICU are usually highly heterogeneous, evidences from real-world clinical data might provide some clues for trials which aim at determining or validating the ideal target of glycemic control, [22][23][24] although it is obvious that what the ideal target of glycemic control could only be answered by clinical trials. Given current available observational studies had either limited sample sizes 10 or specific indications, 12,14 the study used data from a large critical care database and focused on mixed ICU patients, aiming to evaluate the association between blood glucose within 24 hours after ICU admission and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 For these reasons, a glucose target of 140 to 180 mg/dL is reasonable in most critically ill patients. 5,6 ■ COVID-19 AND HYPERGLYCEMIA As of this writing (April 9, 2020), the COVID-19 pandemic has infected more than 1.5 million people worldwide and more than 400,000 in the United States, and these numbers are projected to increase. 6 This increase will come with a high death toll, increased morbidity rates, and an expected surge in the number of critically ill patients.…”
mentioning
confidence: 99%
“…Several studies demonstrated in heterogeneous populations of critically ill patients that increased glucose variability increased ICU and hospital mortality independently of the mean glucose concentration [55][56][57]. In recent years, the concept of time regarding glucose ranges proved to be of significant importance, with patients with normal blood glucose levels more than 80% of the time showing better outcomes [58][59][60]. Patients with or without diabetes may be affected differently by glucose concentrations [61].…”
Section: Glucose Controlmentioning
confidence: 99%